ISSUES AND MANAGEMENT FOR USED DISPOSABLE DIAPERS IN SOLID WASTE IN THE CITY OF KUALA LUMPUR - Noorhalieza Ali; Mohd Rozainee Taib; Ng Pang Soon; Onn Hassan (PERINTIS eJournal, 2021)
Disposable diapers are indispensable in modern societies. Disposing of soiled diapers is a major global environmental problem as they constitute a large percentage of the municipal solid waste. Kuala Lumpur has a population of 1.79 million in an area of just 243 km2. Currently, Kuala Lumpur’s municipal solid waste generation is about 3.500 tonnes per day where it is sent 80 km away to Tagar Sanitary Landfill for disposal through Taman Beringin Transfer Station which has a capacity of 1,700 tonnes per day. Waste characteristics study conducted in April 2016 showed baby disposable diapers contributed to 14.35 weight %, the fourth main composition after food and organics waste (32%), plastics (25%) and paper (17%). Comprehensive sampling conducted in 2001/2002 and 2014 showed the average diapers content was about 5.14 and 10.68 % weight, respectively. This paper looks at the issues of used baby diapers in solid waste, the options for its disposal worldwide such as landfilling, composting, recycling and incinerating with energy generation and then selecting the most sustainable, practical, effective and efficient disposal option for Kuala Lumpur.